2018
DOI: 10.1002/pbc.27567
|View full text |Cite
|
Sign up to set email alerts
|

Pathological prognostication of paediatric adrenocortical tumours: Is a gold standard emerging?

Abstract: Background Criteria for the pathological classification of adult adrenocortical tumours (ACTs) have been found to overestimate the malignant potential of childhood ACTs. We sought to evaluate the accuracy and utility of criteria developed for paediatric ACT compared to current criteria for adults. Methods ACTs treated between January 2006 and December 2016 in two paediatric institutions were evaluated. Patients classified clinically as malignant (CM) had locally invasive disease at surgery requiring extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 16 publications
(30 reference statements)
0
32
0
1
Order By: Relevance
“…Thirty‐six papers 2,5,16–18,20–47,49,50 allowed the evaluation of gender effect on outcome: females were found to have RR of 1.21, without reaching a significance ( P = .14; 95% CI 0.94‐1.55; I 2 0%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐six papers 2,5,16–18,20–47,49,50 allowed the evaluation of gender effect on outcome: females were found to have RR of 1.21, without reaching a significance ( P = .14; 95% CI 0.94‐1.55; I 2 0%).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis (Supporting Information S3) including 13 studies 5,20,23,36,27,32,33,37,38,42,51,53,54 compared the outcome between patients undergone complete resection and those undergone incomplete resection. The first ones showed a better outcome (P < .00001; RR 3.50; 95% CI 2.51-4.88; I 2 16%).…”
Section: Surgery Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: In a recently published article in Pediatric Blood & Cancer , Jehangir et al studied 22 cases of pediatric adrenocortical tumors (ACTs) and found that Wieneke criteria accurately predicted clinical outcome . The authors demonstrated correctly how the Wieneke score was superior compared to adult scores to predict malignancy, which is now recognized in the literature .…”
mentioning
confidence: 99%
“…Assessing the prognostic value of Wieneke score in small series of patients has been done few times but appears to us not sufficient enough to guide perioperative treatment recommandations . Pathologists have to primarily focus on how the pathological grading is integrated by clinicians to decide whether or not an adjuvant therapy is needed.…”
mentioning
confidence: 99%